Sports nutrition enhancing athletic performance - Campbell, Bill I., 1975- (CRC Press/Taylor & Francis, 2014)
This book offers a clear focus on scientifically based sports nutrition advice to maximize performance. It also addresses exercise metabolism, which governs how nutrients exert physiologic effects that lead to increased athletic potential.